Regional differences in the determinants of Oregon VMT. (June 2017) - Ke, Yue; McMullen, B. Starr
Abstract: Road user charges (RUCs) in the form of per mile charges have been suggested as an alternative to fuel taxes to help keep up with the costs of maintaining and expanding public road systems. The success of a RUC in providing for the long term stability of highway finance depends partly on how drivers respond to changes in the tax structure and also other determinants of driving behavior. Region specific characteristics, such as public transit accessibility and biking infrastructure, may also affect vehicle miles traveled (VMT) demand. This paper uses econometric techniques to examine the determinants of VMT using data from the Oregon Household Activities Survey (OHAS). We use standard OLS regression to examine the impact of urban density, household income, fuel cost, transit mileage, household location, and additional household characteristics on VMT. Preliminary results show that statewide Oregon demand for VMT is positively and significantly impacted by household income. Statewide, fuel price, transit use and population density are all found to be statistically significant and negatively related to household VMT. However, at the regional level some of these variables lose significance. Holding all factors constant, household VMT is found to differ by region as well as by population density.